A laesio enormis a római jogban és annak továbbélése során - Sándor, István (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The aim of this study is to provide a comprehensive examination of the historical and comparative legal background of the doctrine of laesio enormis, with particular attention to its roots in ancient legal systems and its subsequent development and integration into European private law throughout the medieval and modern periods. The study analyses the Roman law regulation of laesio enormis, as well as analogous provisions found in Mesopotamian and Jewish law, and explores the treatment of the concept within Christian legal thought. Furthermore, it considers the presence of the doctrine in various modern civil codes and examines the relationship between laesio enormis and the doctrine of consideration as developed in the common law tradition. The study aims to introduce new perspectives on laesio enormis by addressing areas of inquiry that have received less scholarly attention, including the rule’s broader social justification and legitimacy.